Evaluating quality standards' adherence in surgical care: a case study from Pakistan. (27th December 2017) - Fatima, Iram; Humayun, Ayesha; Anwar, Muhammad Imran; Shafiq, Muhammad
Abstract: Objective: To explore the extent of adherence to surgical quality standards and areas of improvement. Design: Multi-method case study was done. Assessment of observed/actual and self-reported adherence to quality standards in surgical care was done on WHO's safe-surgery checklist. Client satisfaction through exit interviews assessed of all operated during 1 month. Semi-structured interviews of key informants were conducted to identify areas of improvements in surgical care in this hospital. Setting: Conducted in a tertiary care teaching hospital in Lahore, Pakistan. Participants: Out of all 154 patients during 1 month were admitted with indications for surgery and 35.71% patients gave consent and participated in the study. Outcome measure: Actual and reported adherence data were categorized in excellent, good, satisfactory and poor adherence to standards. For in-depth interviews, themes were identified from textual data. Results: Overall activities in surgical department were performed well, patients were satisfied and hospital surgical mortality rate was zero but infection control measures needs attention and these practices were found poor with high re-operation and re-admissionrate ( P -value < 0.001). Adherence to standards of surgical quality was inadequate in pre-operative, operative and post-op steps as assessed on the checklist but actual adherence was different from reported adherence by surgical care providers. Conclusion: This case study shows a complete picture of surgical care quality in a hospital of Pakistan. Discrepancy between perceived/reported adherence and actual practice was found. Patients' satisfaction is not a reliable outcome measure of surgical care quality.